2024
DOI: 10.1128/spectrum.03471-23
|View full text |Cite
|
Sign up to set email alerts
|

Single-cell analysis reveals that cryptic prophage protease LfgB protects Escherichia coli during oxidative stress by cleaving antitoxin MqsA

Laura Fernández-García,
Xinyu Gao,
Joy Kirigo
et al.

Abstract: Although toxin/antitoxin (TA) systems are ubiquitous, beyond phage inhibition and mobile element stabilization, their role in host metabolism is obscure. One of the best-characterized TA systems is MqsR/MqsA of Escherichia coli , which has been linked previously to protecting gastrointestinal species during the stress it encounters from the bile salt deoxycholate as it colonizes humans. However, some recent whole-population studies have challenged the role of toxins such as MqsR in bact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 62 publications
0
1
0
Order By: Relevance
“…The results showed that compared with the WT strain, the transcription levels of rpoS , katE and oxyR in DE456Δphi456 were decreased by 2–3 times after H 2 O 2 treatment for 15 min (Figure 8 B). Single-cell analysis revealed that lfgB , a cryptic prophage protease, protects Escherichia coli from oxidative stress by cleaving the antitoxin MqsA to derepress rpoS [ 43 ]. In addition, some prophages have been found to encode superoxide dismutase [ 44 ], an enzyme that catalyzes the conversion of superoxide into hydrogen peroxide and oxygen, thereby enhancing the bacterium's ability to withstand oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that compared with the WT strain, the transcription levels of rpoS , katE and oxyR in DE456Δphi456 were decreased by 2–3 times after H 2 O 2 treatment for 15 min (Figure 8 B). Single-cell analysis revealed that lfgB , a cryptic prophage protease, protects Escherichia coli from oxidative stress by cleaving the antitoxin MqsA to derepress rpoS [ 43 ]. In addition, some prophages have been found to encode superoxide dismutase [ 44 ], an enzyme that catalyzes the conversion of superoxide into hydrogen peroxide and oxygen, thereby enhancing the bacterium's ability to withstand oxidative stress.…”
Section: Discussionmentioning
confidence: 99%